2019
DOI: 10.1051/e3sconf/201911001037
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ettringite morphology on the properties of expanding cement systems

Abstract: The effect of the pH of the reaction solution on the crystallization process and the ettringite morphology is theoretically substantiated and experimentally proved. Using physical and chemical research methods, the dependence of the morphology of crystallizing ettringite on the pH value of the reaction solution was established. It has been established that by introducing mineral micro fillers into the composition of expanding cement, it is possible to actively influence the pH value, the morphology of the resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…When the calcium sulfate concentration is increased from 5% to 20%, the ettringite takes the form of more voluminous needles (Figure 9). This behavior was also observed by Kharchenko et al [26]. These authors studied the variation in ettringite morphology at a constant pH of 11 while changing the CaSO 4 concentration.…”
Section: Scanning Electron Microscopy (Sem/edx)supporting
confidence: 77%
See 1 more Smart Citation
“…When the calcium sulfate concentration is increased from 5% to 20%, the ettringite takes the form of more voluminous needles (Figure 9). This behavior was also observed by Kharchenko et al [26]. These authors studied the variation in ettringite morphology at a constant pH of 11 while changing the CaSO 4 concentration.…”
Section: Scanning Electron Microscopy (Sem/edx)supporting
confidence: 77%
“…At longer hydration times and a 20% concentration, the ettringite needles appear to be longer and slenderer. Kharchenko et al [26] observed that at a pH of around 10, small ettringite needles form, while at pH 12 the needles become intermediate in size.…”
Section: Scanning Electron Microscopy (Sem/edx)mentioning
confidence: 99%
“…Formation of secondary ettringite can cause destruction of concrete due to crystallization pressure on porous sides while volume increases. Advanced freeze-thaw resistance of AABFC concrete in solution of NaCl is caused by the absence of portlandite in hydration products [43] as well as by the absence of ettringite or due to changes in its morphology in highlyalkaline hydration medium from filamentous, needle to prismatic as well as plate shape [44].…”
Section: Introductionmentioning
confidence: 99%